Strategi Komunikasi Wisata: Trend Tiktok Healing Trip Sebagai Simbol Proses Penyembuhan Mental (Studi Pariwisata Telaga Sarangan) - Muhammad Nuqi Nasrul Hakim; Rafandi Budiaji Aryasa; Muhammad Bangun Saputra; Puput Andita; Ferdika Aprilia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The development of social media, particularly TikTok, has generated various popular cultural trends that influence how people interpret daily activities, including tourism practices. One emerging trend is the healing trip, which is often perceived as a form of mental recovery through travel. Natural tourism destinations such as Telaga Sarangan are frequently represented on TikTok as symbolic spaces for mental healing. This study aims to analyze how the TikTok healing trip trend constructs symbols and meanings of mental healing within the context of Telaga Sarangan tourism. Using a qualitative approach, this study employs content analysis of TikTok videos and literature review related to digital communication, popular culture, and health tourism. The findings indicate that healing trips on TikTok are predominantly represented through visual and aesthetic experiences rather than genuine psychological healing processes. Social media plays a significant role in shaping healing as a digital lifestyle, influencing public perceptions of natural tourism functions. This study concludes that healing trips represent a socially constructed meaning mediated by digital platforms rather than a clinical mental recovery process.